Development of real time transaction based android e-ticket application as regional tax monitoring facilities (Case study: Ayu rejeki swimming pool object, probolinggo regency) - M. Mahaputra Hidayat; Vicinthia Veren Sudrajat; Permata Ayu Rahmawati; Muhammad Rizqika Brimadi Haviansyah (Journal Basic Science and Technology, 2023)
There are so many local entertainment tourism objects in the Probolinggo Regency area, this is not spared for the local government to apply an entertainment tax to the taxpayer sector in accordance with the amount of income. However, there are still entertainment tax objects whose ticket sales use a manual system where tickets and taxpayer payments as well as SPTPD reports (Regional Tax Returns) are all written manually. One of them is the Ayu Rejeki Swimming Pool Tourism Object. This is considered ineffective on the part of the taxpayer, and the large amount of tax paid is less accurate on the part of the Probolinggo Regency regional government revenue agency. To overcome this, tax monitoring activities are carried out at the tax object so that the amount of tax deposit paid is in accordance with the results of ticket sales revenue for the tax object. In order to support monitoring activities, a special application was created for Pool Taxpayers Ayu Fortune in the form of Android-based e-Tickets and real-time transactions. The method used to create this e-Ticket application is the REST API; HTTP request methods GET, POST, PUT, and DELETE. The e-Ticket application, which has real-time transaction capabilities, directly records the number of transactions or income in the tax object to the regional tax monitoring dashboard (this will later become the taxpayer's e-SPTPD report) Kab. Probolinggo. Application testing that has been used states that the system records transactions in real time. So it can be concluded that the e-Ticket application is very profitable or very good for both parties with transaction efficiency and automatic SPTPD reports. The Probolinggo Regency regional government revenue agency will also benefit from increased accuracy of tax payments from taxpayers.based on the assessment of the admin or user of this e-ticket application, it gets a score of 95% so that it is an application in the "very good" category.